2015
DOI: 10.12927/hcpol.2015.24210
|View full text |Cite
|
Sign up to set email alerts
|

A National Approach to Reimbursement Decision-Making on Drugs for Rare Diseases in Canada? Insights from Across the Ponds

Abstract: Introduction: Regardless of the type of health system or payer, coverage decisions on drugs for rare diseases (DRDs) are challenging. While these drugs typically represent the only active treatment option for a progressive and/or life-threatening condition, evidence of clinical benefit is often limited because of small patient populations and the costs are high. Thus, decisions come with considerable uncertainty and risk. In Canada, interest in developing a pan-Canadian decision-making approach informed by int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…Similar to Canada, most 20 OECD countries with a socially funded health care system or universal health care do not have a national program for funding DRDs, except for the United Kingdom. Instead, many apply a “safety net” program or use modified decision criteria when their common drug review processes are insufficient for funding decisions for DRDs [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to Canada, most 20 OECD countries with a socially funded health care system or universal health care do not have a national program for funding DRDs, except for the United Kingdom. Instead, many apply a “safety net” program or use modified decision criteria when their common drug review processes are insufficient for funding decisions for DRDs [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to ICER's consideration of the type of health technology, ICER also considers modifications to its methods for assessing value for treatments of serious, ultra-rare disorders and high-impact single-administration or short-term therapies. Most often, HTA agencies make recommendations for rare disease drugs based on the same centralized national review process as other drugs 33 ; however, several HTA bodies have created separate mechanisms, adapted existing processes, 29,33 and/or added "safety nets" that allow for individual patient requests for access to medicines that do not receive a positive reimbursement requests. 33 These alternatives have arisen primarily because orphan drugs are not able to meet typical cost-effectiveness standards, including high costs and uncertainty in the clinical evidence.…”
Section: Type Of Medical Conditionmentioning
confidence: 99%
“…Most often, HTA agencies make recommendations for rare disease drugs based on the same centralized national review process as other drugs 33 ; however, several HTA bodies have created separate mechanisms, adapted existing processes, 29,33 and/or added "safety nets" that allow for individual patient requests for access to medicines that do not receive a positive reimbursement requests. 33 These alternatives have arisen primarily because orphan drugs are not able to meet typical cost-effectiveness standards, including high costs and uncertainty in the clinical evidence. 34,35 A study of 32 countries (mostly European) found that 41% of countries had a supplemental process for rare or ultra-rare disease treatments, and the countries were classified based on the extent to which these processes were integrated with standard HTA processes.…”
Section: Type Of Medical Conditionmentioning
confidence: 99%
“…
Fig. 1 Rare disease patient organisation roles and responsibilities in therapeutic innovation (information from [ 14 , 15 , 21 , 23 ])
…”
Section: Introductionmentioning
confidence: 99%